EFEKTIVITAS PENGGUNAAN MEDIA DIGITAL DALAM PEMBELAJARAN SOSIOLOGI DI SEKOLAH MENENGAH ATAS - Fara Khansa Ameliasari; Alvianto; Aisyah Yusifa Jannah; Allysa Dwihastuti Fatihatu Zulfa; Clara Putri Natalie Boreel; Fidya Mar’ie Al Mufti; Siany Indria Liestyasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The rapid development of digital technology has led to a transformation in the field of education, including in the subject of sociology at secondary school level. Sociology is abstract, conceptual, and contextual in nature, so a relevant teaching approach is required. This article aims to examine and analyse the effectiveness of using digital media in sociology lessons at secondary school level through a Systematic Literature Review (SLR) approach. The results of the study show that the use of digital media in sociology lessons at secondary school level is very diverse, including gamification platforms (Gimkit, Kahoot, Wordwall), interactive visual media (Canva), online platforms (Microsoft Sway, blogs), and video-based media (YouTube, animated videos). The use of these various media has been shown to be effective in increasing the motivation, interest, and learning outcomes of students. In terms of motivation and interest, gamification-based media can create a more enjoyable learning environment, making students more enthusiastic. In terms of improving learning outcomes, visual media, video tutorials, and online platforms can help students understand sociological concepts through concrete visualisation. These findings suggest that integrating digital media into teaching, particularly in sociology, is an effective way to overcome the limitations of traditional approaches and support 21st-century learning that is relevant and contextual.